Evaluating the impacts of mesoscale eddies on abundance and distribution of neon flying squid in the Northwest Pacific Ocean - Zhang, Yuchen; Yu, Wei; Chen, Xinjun; Zhou, Mo; Zhang, Chunling (Frontiers in Marine Science, 2022)
Mesoscale eddies are ubiquitous in global oceans yielding significant impacts on marine life. As a short-lived pelagic squid species, the population of neon flying squid (Ommastrephes bartramii) is extremly sensitive to changes of ambient oceanic variables.. However, a comprehensive understanding of how mesoscale eddies affect the O. bartramii population in the Northwest Pacific Ocean is still lacking. In this study, a 10-year squid fisheries data with eddy tracking and high-resolution reanalysis ocean reanalysis data were combined to evaluate the impact of mesoscale eddies and their induced changes in environmental conditions on the abundance and habitat distribution of O. bartramii in the Northwest Pacific Ocean. A weighted-based habitat suitability index (HSI) model was developed with three crucial environmental factors: sea surface temperature (SST), seawater temperature at 50-m depth (T50m) and chlorophyll-a concentration (Chl-a). During years with an unstable Kuroshio Extension (KE) state, the abundance of O. bartramii were significantly higher in anticyclonic eddies (AEs) than that in cyclonic eddies (CEs). This difference was well explained by the distribution pattern of suitable habitats in eddies derived from the HSI model. Enlarged ranges of the preferred SST, T50m and Chl-a for O. bartramii within AEs were the main causes of more squids to occurring inside the warm-core eddies, whereas highly productive CEs matching with unfavorable thermal conditions tended to form unsuitable habitats for O. bartramii. Our findings suggest that with an unstable KE background, suitable thermal conditions combined with favorable foraging conditions within AEs were the main drivers that yielded the high abundance of O. bartramii in the warm eddies.